(3GdGSJQGJjLjI GdJShjbjI ddehGfF h TQcGJ Gdfbd GdHMQjs - (3eMeO(B, (3YHO GdaJGMs ((3GdbGgQI(B:s (3GdecJH GdYQHj ddeYGQa(B,s, 2011)
(3GSJbUGA bjGS aYGdjI fXGe GdJNWjW GdESJQGJjLj, eG GdejfGA , JbSjeGJ GdejfGA h SdWGJg , GdhGLHGJ GdQFjSjI dLgGR GOGQIGdejfGA , hXGFa GdejfGA h eSFhdjGJ GdeSJhjGJ GdGOGQjI HLgGR GdejfGA , CTcGd GdQbGHI Ydi GdehGfF GdHMQjI , TQcGJ Gdfbd GdHMQj h Tcd GdedcjI aj TQcGJ Gdfbd GdHMQj, GdGSJQGJjLjGJ GdGOGQjI, GSJQGJjLjGJ GdJShjb h GdeRjL GdJShjbj h CNjQG GYOGO GdGSJQGJjLjI GdJShjbjI dTQcGJ Gdfbd GdHMQj h eQGMdgGs
(3HHdjhZQGajG(B: (3U(B.260-261 (3cTGa eUWdMGJ U(B.221s
Keywords: (3GdJShjbs; (3GdehGfFs; (3Gdfbd GdHMQjs